2004
DOI: 10.1021/tx0497696
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2A-Catalyzed Metabolic Activation of Structurally Similar Carcinogenic Nitrosamines:  N‘-Nitrosonornicotine Enantiomers, N-Nitrosopiperidine, and N-Nitrosopyrrolidine

Abstract: N'-Nitrosonornicotine (NNN) and N-nitrosopiperidine (NPIP) are potent esophageal and nasal cavity carcinogens in rats and pulmonary carcinogens in mice. N-Nitrosopyrrolidine (NPYR) induces mainly liver tumors in rats and is a weak pulmonary carcinogen in mice. These nitrosamines may be causative agents in human cancer. alpha-Hydroxylation is believed to be the key activation pathway in their carcinogenesis. P450 2As are important enzymes of nitrosamine alpha-hydroxylation. Therefore, a structure-activity relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 54 publications
1
94
0
Order By: Relevance
“…Mouse P450 2A5 is an excellent catalyst of 5′-hydroxylation of both (R)-and (S)-NNN, and several other P450 2A enzymes including rat 2A3, mouse 2A4, human 2A6, and human 2A13 are also reasonably efficient (30). Lower activity of P450 2A enzymes was found for 2′-hydroxylation of (R)-NNN, and none was found for 2′-hydroxylation of (S)-NNN.…”
Section: Tobacco-specific Nitrosamines: Metabolism Dna Adduct Formatmentioning
confidence: 98%
“…Mouse P450 2A5 is an excellent catalyst of 5′-hydroxylation of both (R)-and (S)-NNN, and several other P450 2A enzymes including rat 2A3, mouse 2A4, human 2A6, and human 2A13 are also reasonably efficient (30). Lower activity of P450 2A enzymes was found for 2′-hydroxylation of (R)-NNN, and none was found for 2′-hydroxylation of (S)-NNN.…”
Section: Tobacco-specific Nitrosamines: Metabolism Dna Adduct Formatmentioning
confidence: 98%
“…CYP2A5 is active toward numerous drugs and other xenobiotic compounds (Su and Ding, 2004;Wong et al, 2005;Raunio et al, 2008), including many nasal toxicants, such as the herbicide dichlobenil and the antithyroid drug methimazole . Previous studies using recombinant P450 enzymes have shown that human CYP2A6 and CYP2A13, orthologs of mouse CYP2A5, are both active in NA bioactivation (Cho et al, 2006;Fukami et al, 2008); however, evidence for a role of CYP2A5 in mediating the toxicity of NA has yet to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, CYP2A6 and CYP2A13 are important catalysts of NNN and NNK ␣-hydroxylation (Jalas et al, 2005;Wong et al, 2005a). The high efficiency of CYP2A13 for NNK metabolic activation combined with its expression in respiratory tissues, including nasal mucosa, lung, and trachea, suggests that CYP2A13 plays a critical role in tobacco-specific nitrosamine-induced carcinogenesis (Su et al, 2000;Jalas et al, 2005;Wong et al, 2005b;Zhu et al, 2006).…”
mentioning
confidence: 99%